1998
DOI: 10.1111/j.1749-6632.1998.tb09740.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Systems Underlying Arousal and Attention: Implications for Drug Abusea

Abstract: The monoaminergic and cholinergic systems are implicated in different forms of behavioral arousal that can be dissected in terms of their forebrain targets and the nature of the behavioral processes they modulate in distinct regions. Thus, evidence in rats with selective neurochemical manipulations tested behaviorally using an analog of an attentional task developed for human subjects indicates that the coeruleo-cortical noradrenergic system is implicated in divided and selective attention, the basal forebrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 38 publications
2
102
0
Order By: Relevance
“…A previous study (Robbins et al 1998) also reported effects of intra-mPFC scopolamine on the 5CSRTT. These authors found that a 10-µg dose of scopolamine significantly reduced attentional accuracy as well as impairing other aspects of performance.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study (Robbins et al 1998) also reported effects of intra-mPFC scopolamine on the 5CSRTT. These authors found that a 10-µg dose of scopolamine significantly reduced attentional accuracy as well as impairing other aspects of performance.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, dopamine application increases signal-to-noise ratio of striatal firing rates in vivo (Rolls, 1984;reviewed by Servan-Schreiber et al, 1998a). In addition, pharmacological studies with dopamine agonists and antagonists indicate that dopamine decreases reaction times for behavioral responses and is involved in behavioral activation (Salamone et al, 1997;Robbins et al, 1998). In the proposed model, manipulations of dopamine concentration in the matrisomes have a complex influence on the number of acts in the exploration phase, since the simulated dopamine effects on elevated and on hyperpolarized membrane potentials are antagonistic and therefore sensitive to model parameters values (unpublished results).…”
Section: Striatal Dopamine Concentrationmentioning
confidence: 94%
“…The scopolamine effect was one of the earliest showing that cortical arousal and behavioral arousal were different (Longo, 1956). Drugs such as diazepam (an anxiolytic), clonidine (an antihypertensive), and haloperidol (an antiemetic) have such different effects that a unitary construct such as diminished arousal or "sedation" has been shown to be inadequate (Robbins et al, 1998). From a neural systems perspective, arousal processes are clearly not unitary; multiple sources of arousal interact in the brain, and have different kinds of effects on the mind and body, while details of their functioning continue to be elucidated.…”
Section: Evidence For a Theory Of Multiple Arousalsmentioning
confidence: 99%